2020
DOI: 10.3389/fnins.2020.586107
|View full text |Cite
|
Sign up to set email alerts
|

Anti-sortilin1 Antibody Up-Regulates Progranulin via Sortilin1 Down-Regulation

Abstract: Progranulin (PGRN) haploinsufficiency associated with loss-of-function mutations in the granulin gene causes frontotemporal dementia (FTD). This suggests that increasing PGRN levels could have promising therapeutic implications for patients carrying GRN mutations. In this study, we explored the therapeutic potential of sortilin1 (SORT1), a clearance receptor of PGRN, by generating and characterizing monoclonal antibodies against SORT1. Anti-SORT1 monoclonal antibodies were generated by immunizing Sort1 knockou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 68 publications
1
15
0
2
Order By: Relevance
“… 48 Thus, sortilin has become a hot target for FTLD- GRN therapeutics to boost circulating PGRN levels. Small molecules and anti-sortilin antibodies have been developed to inhibit PGRN–sortilin interaction and anti-sortilin antibodies are currently in clinical trials for FTLD- GRN 49–51 (NCT04111666, NCT04374136, NCT03987295). Recent studies have shown that anti-sortilin antibodies not only block PGRN–sortilin interaction but also downregulate sortilin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 48 Thus, sortilin has become a hot target for FTLD- GRN therapeutics to boost circulating PGRN levels. Small molecules and anti-sortilin antibodies have been developed to inhibit PGRN–sortilin interaction and anti-sortilin antibodies are currently in clinical trials for FTLD- GRN 49–51 (NCT04111666, NCT04374136, NCT03987295). Recent studies have shown that anti-sortilin antibodies not only block PGRN–sortilin interaction but also downregulate sortilin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that anti-sortilin antibodies not only block PGRN–sortilin interaction but also downregulate sortilin levels. 49 However, given the critical role of PGRN and granulin peptides in the lysosome 10 , 22 and the fact that GRN mutations in FTLD also cause haploinsufficiency of granulin peptides, 33 restoration of both extracellular and lysosomal pools of PGRN in the brain of FTLD- GRN patients will be needed to have better therapeutic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…SORT1 is a potential target to correct PGRN reduction (Miyakawa et al., 2020). The therapeutic potential of SORT1 was developed by generating and characterizing monoclonal antibodies that downregulate SORT1.…”
Section: Increasing Pgrn Level To Prevent Neurodegeneration In Dementiamentioning
confidence: 99%
“…70 Similarly, down-regulation of sortilin 1 (SORT1) expression is a pivotal mechanism of PGRN elevation and a prospective target for PGRN to promote arthritis and other diseases, as indicated by PGRN KO mice phenotype. 98 As for the protection of PGRN from proteolytic degradation, some proteins, such as the secretory leukocyte protease inhibitor (SLPI) and apolipoprotein A1 can bind to it to protect it against proteolytic degradation. 34 Besides, an engineered protein consisted of the FAC domain of PGRN was constructed, which retains comparable TNFR binding affinity of PGRN referred as Atsttrin.…”
Section: Pgrn As a Promising Therapeutic Target For Immune-mediated Diseasesmentioning
confidence: 99%